STRATEGI PENDIDIKAN ANTI KORUPSI DALAM PERSPEKTIF TEORI PENDIDIKAN KRITIS PAULO FREIRE: Anti-Corruption Education Strategy From The Perspective Of Paulo Freire's Critical Education Theory - Abdulloh, Abdulloh (STAI Ma'had Aly Al-Hikam Malang, 2025)
Corruption in Indonesia has become a systemic issue that permeates nearly all aspects of social, political, and bureaucratic life. Efforts to combat it through educational pathways have largely been dominated by normative and indoctrinative approaches, lacking critical reflection. This article proposes an alternative framework through the lens of Paulo Freire’s critical pedagogy, which emphasizes conscientização (critical consciousness), dialogical learning, and active student participation in deconstructing the social injustices that sustain corrupt practices. Employing a library research method, the article analyzes relevant literature to formulate a transformative anti-corruption education strategy. Findings indicate that anti-corruption education must be designed to be contextual, reflective, and collaborative, so that values of integrity are not merely memorized but embedded in students' critical awareness and ethical actions. The role of teachers as facilitators, the integration of anti-corruption themes across disciplines, and the use of creative media are identified as key success factors. Thus, education can serve as a site of liberation and empowerment in the fight against systemic corruption.